Enrico Castellani - Corà, Bruno 1942-; Vettese, Angela 1959-; Luzi, Mario 1914-2005; Villa, Emilio 1914-2003 (Dominique Lévy, 2016)
Showcasing the paintings of influential Italian artist 'Enrico Castellani' (born 1930), this publication presents his first solo exhibition in London. Castellani's large-scale relief canvases are placed in dialogue with his more recent angular, metallic paintings
Catalog of an exhibition held at Dominique Lévy, London, February 9 - March 26, 2016 and New York, April 7 - May 21, 2016. - Includes interview with the artist, conducted by Hans Ulrich Obrist. - Includes bibliographical references
Keywords: Castellani, Enrico / 1930- / Exhibitions; Castellani, Enrico / 1930- / Interviews; Castellani, Enrico -- 1930-2017; Geschichte 1961-2007; Painting, Italian; Malerei; Ausstellungskatalog; Ausstellungskatalog -- Dominique Lévy -- 07.04.2016-21.05.2016 -- New York, NY; Ausstellungskatalog -- Dominique Lévy -- 09.02.2016-26.03.2016 -- London